Association of polychlorinated biphenyls and organochlorine pesticides with autism spectrum disorder in Jamaican children. (August 2020) - Bach, MacKinsey A.; Samms-Vaughan, Maureen; Hessabi, Manouchehr; Bressler, Jan; Lee, MinJae; Zhang, Jing; Shakespeare-Pellington, Sydonnie; Grove, Megan L.; Loveland, Katherine A.; Rahbar, Mohammad H.
Highlights: We report inverse association of PCB-153 & PCB-180 concentrations with ASD in Jamaica. Differences in diet between ASD and TD controls may play a role in these findings. The association of PCB-153 levels with ASD status may be modified by GSTM1 genotype. Abstract: Background: Polychlorinated biphenyls (PCBs) and organochlorine (OC) pesticides are suspected to play a role in autism spectrum disorder (ASD). Objectives: To investigate associations of PCBs and OC pesticides with ASD in Jamaican children and explore possible interaction between PCBs or OC pesticides with glutathione S -transferase (GST) genes ( GSTT1, GSTM1, GSTP1 ) in relation to ASD. Methods: Participants included n = 169 age- and sex-matched case-control pairs of Jamaican children 2−8 years old. Socioeconomic status and food frequency data were self-reported by the parents/guardians. Blood from each participant was analyzed for 100 PCB congeners and 17 OC pesticides and genotyped for three GST genes. PCBs and OC pesticides concentrations below the limit of detection (LoD) were replaced with (LoD/ √ 2 ) . We used conditional logistic regression (CLR) models to assess associations of PCBs and OC pesticides with ASD, individually or interactively with GST genes ( GSTT1, GSTM1, GSTP1 ). Results: We found inverse associations of PCB-153 [adjusted MOR (95 % CI) = 0.44 (0.23, 0.86)] and PCB-180 [adjusted MOR (95 % CI) = 0.52 (0.28, 0.95)] with ASD. When adjusted for covariates in a CLR the interaction between GSTM1 and PCB-153 became significant ( P  <  0.01). Discussion: Differences in diet between ASD and typically developing control groups may play a role in the observed findings of lower concentrations of PCB-153 and PCB-180 in individuals with ASD than in controls. Considering the limited sample size and high proportion of concentrations below the LoD, these results should be interpreted with caution but warrant further investigation into associations of PCBs and OC pesticides with ASD.